1991
DOI: 10.1002/jrs.1250220102
|View full text |Cite
|
Sign up to set email alerts
|

Raman investigation of simple and complex oxides of platinum

Abstract: and MPt,O, (M = Mn, Co, Cd). An enumeration of the allowed Raman modes is made for all of these oxides except Pt,O, , for which the structure is unknown. Polarization measurements allow symmetry species assignments to be made for the lines from a-PtO, and PtCoO, , and a likely assignment of the lines from /l-PtO, is made by analogy with rutile-structured materials with the rutile structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 21 publications
7
30
0
1
Order By: Relevance
“…[81] this band was assigned to PtÀOv ibrations. The spectrum of PtO oxide reported in [82] for excitation at 457.9 nm also showed ab and at 670 cm À1 .T here, also the second band is presenti nt he spectrum at 438 cm À1 ,w hich in our case overlaps with the main peak attributed to F 2g vibration of ceria. The largest amounto fP to xides is detectedi n the Raman spectra of the samples calcined at 600-800 8C; upon calcination at 1000 8C, only the main F 2g band is observed, which corresponds to virtuallyc omplete annealing and crystallization of platinum and ceria particles.…”
Section: Raman Spectroscopy Studysupporting
confidence: 68%
See 1 more Smart Citation
“…[81] this band was assigned to PtÀOv ibrations. The spectrum of PtO oxide reported in [82] for excitation at 457.9 nm also showed ab and at 670 cm À1 .T here, also the second band is presenti nt he spectrum at 438 cm À1 ,w hich in our case overlaps with the main peak attributed to F 2g vibration of ceria. The largest amounto fP to xides is detectedi n the Raman spectra of the samples calcined at 600-800 8C; upon calcination at 1000 8C, only the main F 2g band is observed, which corresponds to virtuallyc omplete annealing and crystallization of platinum and ceria particles.…”
Section: Raman Spectroscopy Studysupporting
confidence: 68%
“…Similar vibrations at 125 and 300 cm À1 were detectedb y Graham et al in the spectra of the 2.7 %Pt/g-Al 2 O 3 catalyst. [82] The authors concluded that such vibrations cannot be attributed to certain structures of platinum oxidesa nd supposed the formation of the surfaceo xide. Thus, the Raman spectra in the present work indicate that calcination of the mixture of ceria and platinum NPs at 600-800 8Cr esults in the formationofsurface platinum oxides PtO and PtO x .T he oxidized speciesP tO x may be structurally related with ceria because such effects in Ramans pectra (vibrations near 200 cm À1 )w ere detected for cerium oxides promoted with Pd, [83,84] Ni, [85] Cu, [86] and Rh [87] cations.T he emergence of additional vibrations at 300 cm À1 and manifestation of the resonance effect for the vibration at 153 cm À1 upon excitation at 785 nm after calcination at 800 8C may be related to additional ordering and coarsening of the oxidizedp latinum clusterso nt he cerias urfaceo rt hose encapsulatedins ubsurface cerialayers.…”
Section: Raman Spectroscopy Studymentioning
confidence: 99%
“…It and the actual vacancy density are likely dependent on the details of sample preparation, and as such the use of Raman shifts and linewidths as a diagnostic of particle size should be limited to a given preparation method. 23 The variations of the phonon frequency and linewidth up to RT definitively show that phonon coupling is not the reason for the increasing peak red shift and broadening with decreasing particle size. If enhanced phonon coupling in the nanoparticles were the reason for these lineshape changes, then the nanoparticle shift and width at low temperature would be relatively much closer to those for the larger particles.…”
Section: Discussionmentioning
confidence: 88%
“…However, the results of electron-microprobe analysis indicate that the grain is actually a mixture of at least two, and may be more, different phases. The peak at 657 cm − 1 and the shape of the surrounding spectral region strongly resemble the Raman spectra typical of the synthetic mono-oxides PtO and PdO (Weber et al, 1988;Graham et al, 1991), suggesting that a (Pt, Pd, Fe)O phase could be the most abundant component of the grain from Nurali. However, results of the Raman analysis apparently allow more reliable conclusions to be drawn.…”
Section: Possible Existence Of Pge Oxides-hydroxides In Naturementioning
confidence: 67%
“…Palladium correlates positively with Cu and negatively with Ni, Fe, and Pt. (Graham et al, 1991) (b) and palladinite (Weber et al, 1988) (c). This conclusion is also supported by the fact that Pd and Cu are mainly concentrated in the rim of the grain (Fig.…”
Section: Alteration Of Pgm and Pge Mobilitymentioning
confidence: 99%